Nyeri pada Pasien Post Op Fraktur Ekstremitas Bawah dengan Pelaksanaan Mobilisasi dan Ambulasi Dini - Juli Andri; Henni Febriawati; Padila Padila; Harsismanto J; Rahayu Susmita (Journal of Telenursing (JOTING), 2020)
The purpose of this study was to determine the relationship between the level of pain with the implementation of early mobilization and early ambulation in post-op fracture patients with lower extremities in the Seruni room of RSUD dr. M. Yunus, Bengkulu. The research design used in this study was a cross-sectional design. The results of the study, patients who did mobilization activities amounted to 82.9%. Patients who did not mobilize to 17.1% of patients who carried out ambulation activities amounted to 82.9%. Patients who did not perform ambulation activities amounted to 17.1%, pain moderate amounted to 77.1%, and severe pain amounted to 22.9%. In the chi-square test results, the value of p-value = 0,000. In conclusion, there is a correlation between the implementation of mobilization and early ambulation with pain in post-op patients with lower limb fractures at RSUD Dr. M. Yunus. Keywords: Early Ambulation, Mobilization, Pain